Graham Dixon interviewed by Rob Willis in Rob and Olya Willis folklore collection - Dixon, Graham, 1948-; Willis, Rob, 1944- (1997)
Graham Dixon who talks about life in Lithgow, N.S.W. and working at the local Small Arms Factory. Graham Dixon speaks of coming to Lithgow, N.S.W. ; the positions he held as Personnel Officer and then Administrator Manager at Australian Defence Industries(A.D.I.) located at Lithgow. Dixon provides an interesting comment re role of the Small Arms Factory in arms production. He tells of being given the job of forming the Museum on the history of the Small Arms Factory and production of firearms by the management of A.D.I.; assistance from the community steering committee-feasibility project; the incorporation & opening of the Museum in Oct. 1985; the attitude of the Lithgow community to the Museum.
Separate interviews with Arthur Ford and Colin Southall are also recorded on this tape.
Recorded on July 4, 1997 at Lithgow, NSW.
Digital master available
Timed summary available (2 p.)
Keywords: Dixon, Graham, -- 1948- -- Interviews; Small Arms Factory (Lithgow, N.S.W.); Australian Defence Industries (Lithgow, N.S.W.) .; Australian Defence Industries (Lithgow, N.S.W.) -- Museums; Military museums -- New South Wales -- Lithgow; Defense industries -- New South Wales -- Lithgow -- Employees -- Interviews